Researching in Black Education Spaces: Contemplating the Consequentiality of the Research Site in Qualitative Education Research - Samiha Rahman; Wintre F. Johnson (International Journal of Qualitative Methods)
Qualitative methodologies that interrogate issues concerning Black children, youth, and school often reify deficit narratives. In stark contrast, we begin with the ontological reality and axiomatic truth of Black humanity—an unquestionable understanding that, regardless of how they may be viewed from the dominant, white gaze, Black people are indeed fully human and capable of robust intellectual achievement. In this article, we detail the ways we have taken up this epistemology in our research and address the following question: What are the methodological affordances of conducting qualitative research in Black Education Spaces? We describe two studies that utilize qualitative methodologies to delineate the expansive capabilities of children and youth across the African diaspora. The first study examined the educational experiences, self-making practices, and lifeworlds of Black American Muslim youth who journeyed to Senegal for Islamic education. The second study, which took place in the U.S., investigated the racial awareness sociopolitical perspectives, and literacy practices of five African American first graders. Taken together, these two studies elucidate that a full understanding of Black education and Black children and youth’s knowledges is most possible when conducting research in Black Education Spaces and that researchers must be accountable to the (Black) communities with whom we conduct research. We, therefore, highlight the necessity for qualitative methodologies that are engaged in a conceptualization of Blackness that is complex and dynamic, and which engages in reciprocal relationship with Black children, youth, and communities.